Improving Students’ Didactic Competences Based on Interactive Educational Methods in The Process of Independent Work - Yulchiyeva Dildora Khabibullayevna (Journal of Social Sciences and Humanities Research Fundamentals, 2026)
This study examines the improvement of students' didactic competences through the use of interactive educational methods in the process of independent work. Modern education emphasizes student-centered learning, where independent activities play a key role in developing critical thinking, self-regulation, and practical skills. The application of interactive methods such as problem-based tasks, discussions, case studies, and collaborative learning enhances students’ engagement and motivation. These approaches help learners effectively organize knowledge, analyze information, and apply theoretical concepts in practice. As a result, interactive independent learning contributes to the development of stronger didactic competences and prepares students for continuous learning and professional development.